Influence of a Deflectable Leading-Edge on a Flapping Airfoil - Camacho, Emanuel A. R. (2023)
Flapping wing dynamics are of great interest in many research areas, such as bioinspired systems and aircraft aeroelasticity. The findings of the present study provide significant insight into the importance of the leading-edge dynamic incidence on the propulsive performance of flapping airfoils. The main objective is to improve the propulsive characteristics by adding a pitching leading-edge to a conventional NACA0012 airfoil at the lower spectrum of the Reynolds number. The problem is solved numerically at a Reynolds number of 104 under various flapping conditions. The results show that the leading-edge pitching amplitude has a great impact on the propulsive power and efficiency, providing meaningful improvements. The required power coefficient is reduced overall, although not as significantly as the propulsive power. The influence of the movable leading-edge on the pressure distribution is analyzed, showing that the enlargement of the frontal area is the root cause of propulsive augmentation. The proposed geometry provides an innovative way of flapping an airfoil with propulsive purposes, offering remarkable improvements that can defy conventional flapping.